STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN PADA ANAK USIA DINI DALAM BENTUK PERMAINAN - Pratiwi Rambung; Novita, Hanabel kadatuan, Sri Hastuti, Novril Dita Yola (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Christian Religious Education (PAK) in early childhood is an important foundation in the formation of faith, character, and spirituality of children from an early age. Early childhood has unique developmental characteristics, namely learning through concrete experiences and playing. Therefore, an interactive and fun learning approach is very relevant. This study aims to examine the PAK learning strategy in the form of games and analyze the effectiveness and challenges of its implementation. Using a descriptive qualitative approach, data was obtained through interviews, observations, and documentation of Christian PAUD teachers in Yogyakarta. The results of the study showed that types of games such as role-playing Bible characters, picture stories, spiritual art activities, praise songs, and nature exploration were able to instill values of faith effectively. The role of teachers is very significant as facilitators, designers, and spiritual guides in learning. However, challenges such as limited media, lack of teacher training, and low parental involvement need to be overcome through ongoing training, provision of contextual media, and strategic communication between schools and families. Game-based learning strategies have been shown to be able to create cognitively, affectively, and spiritually meaningful learning experiences for children. Therefore, this approach is worthy of being developed as a PAK learning model in Christian PAUD environments on an ongoing basis.